Edukasi Masyarakat dalam Meningkatkan Pengetahuan tentang Stunting di Desa Lembang Maroson - Darlis, Idhar; Elyanovianti; Rahayu, Yuli (Window of Community Dedication Journal, 2022)
One of the major problems facing the world today is the incidence of stunting in children under five. WHO predicts that 127 million children under the age of 5 will be stunted by 2025. Stunting is when a child is shorter than other children their age, or in other words, their height is below the standard. The standard used as a reference is the growth curve created by the World Health Organization (WHO). The purpose of this activity is to increase community knowledge related to stunting and its impact and how to overcome it. The methods used in this activity were lectures and discussions. With the number of counseling participants as many as 25 residents. The results obtained after counseling are that the level of knowledge of residents increases regarding stunting and its impact and how to overcome it, Suggestions to residents are expected to disseminate information that has been obtained to other communities.